AtU2AF65b functions in abscisic acid mediated flowering via regulating the precursor messenger RNA splicing of ABI5 and FLC in Arabidopsis. Issue 1 (18th March 2019) - Xiong, Feng; Ren, Jing‐Jing; Yu, Qin; Wang, Yu‐Yi; Lu, Chong‐Chong; Kong, Lan‐Jing; Otegui, Marisa S.; Wang, Xiu‐Ling
Summary: In mammalians and yeast, the splicing factor U2AF65/Mud2p functions in precursor messenger RNA (pre‐mRNA) processing. Arabidopsis AtU2AF65b encodes a putative U2AF65 but its specific functions in plants are unknown. This paper examines the function of AtU2AF65b as a negative regulator of flowering time in Arabidopsis . We investigated the expression and function of AtU2AF65b in abscisic acid (ABA)‐regulated flowering as well as the transcript abundance and pre‐mRNA splicing of flowering‐related genes in the knock‐out mutants of AtU2AF65b . The atu2af65b mutants show early‐flowering phenotype under both long‐day and short‐day conditions. The transcript accumulation of the flowering repressor gene FLOWERING LOCUS C ( FLC ) is reduced in the shoot apex of atu2af65b, due to both increased intron retention and reduced transcription activation. Reduced transcription of FLC results, at least partially, from the abnormal splicing and reduced transcript abundance of ABSCISIC ACID‐INSENSITIVE 5 ( ABI5 ), which encodes an activator of FLC in ABA‐regulated flowering signaling. Additionally, the expression of AtU2AF65b is promoted by ABA. Transition to flowering and splicing of FLC and ABI5 in the atu2af65b mutants are compromised during ABA‐induced flowering. ABA‐responsive AtU2AF65b functions in the pre‐mRNA splicing of FLC and ABI5 in shoot apex, whereby AtU2AF65b is involved in ABA‐mediated flowering transition in Arabidopsis .